Subtype‐Guided 18F‐FDG PET/CT in Tailoring Axillary Surgery Among Patients with Node‐Positive Breast Cancer Treated with Neoadjuvant Chemotherapy: A Feasibility Study. (11th December 2019) - Wu, Siyu; Wang, Yujie; Li, Jianwei; Zhang, Na; Mo, Miao; Klimberg, Suzanne; Kaklamani, Virginia; Cochet, Alexandre; Shao, Zhiming; Cheng, Jingyi; Liu, Guangyu
Abstract: Background: The purpose of this study was to investigate the value of 18 [F]‐fluorodeoxyglucose ( 18 F‐FDG) positron emission tomography/computed tomography (PET/CT) in tailoring axillary surgery by predicting nodal response among patients with node‐positive breast cancer after neoadjuvant chemotherapy (NAC). Methods: One hundred thirty‐three patients with breast cancer with biopsy‐confirmed nodal metastasis were prospectively enrolled. 18 F‐FDG PET/CT scan was performed before NAC (a second one after two cycles with baseline maximum standardized uptake value [SUVmax ] ≥2.5), and a subset of patients underwent targeted axillary dissection (TAD). All the patients underwent axillary lymph node dissection (ALND). The accuracy was calculated by a comparison with the final pathologic results. Results: With the cutoff value of 2.5 for baseline SUVmax and 78.4% for change in SUVmax, sequential 18 F‐FDG PET/CT scans demonstrated a sensitivity of 79.0% and specificity of 71.4% in predicting axillary pathologic complete response with an area under curve (AUC) of 0.75 (95% confidence interval, 0.65–0.84). Explorative subgroup analyses indicated little value for estrogen receptor (ER)‐negative, human epidermal growth factor receptor 2 (HER2)‐positive patients (AUC, 0.55; sensitivity, 56.5%; specificity, 50.0%). Application of 18 F‐FDG PET/CT could spare 19 patients from supplementary ALNDs and reduce one of three false‐negative cases in TAD among the remaining patients without ER‐negative/HER2‐positive subtype. Conclusion: Application of the subtype‐guided 18 F‐FDG PET/CT could accurately predict nodal response and aid in tailoring axillary surgery among patients with node‐positive breast cancer after NAC, which includes identifying candidates appropriate for TAD or directly proceeding to ALND. This approach might help to avoid false‐negative events in TAD. Implications for Practice: This feasibility study showed that 18 [F]‐fluorodeoxyglucose ( 18 F‐FDG) positron emission tomography/computed tomography (PET/CT) could accurately predict nodal response after neoadjuvant chemotherapy (NAC) among patients with breast cancer with initial nodal metastasis except in estrogen receptor‐negative, human epidermal growth factor receptor 2‐positive subtype. Furthermore, the incorporation of 18 F‐FDG PET/CT can tailor subsequent axillary surgery by identifying patients with residual nodal disease, thus sparing those patients supplementary axillary lymph node dissection. Finally, we have proposed a possibly feasible flowchart involving 18 F‐FDG PET/CT that might be applied in post‐NAC axillary evaluation. Abstract : This article evaluates whether 18[F]‐fluorodeoxyglucose positron emission tomography/computed tomography can serve as a tool in tailoring axillary surgery, including targeted axillary dissection or axillary lymph node dissection after neoadjuvant chemotherapy.